CMR derived left ventricular intraventricular pressure gradients identify different patterns associated with prognosis in patients with dilated cardiomyopathy. (3rd October 2022) - Vos, J L; Raafs, A G; Henkens, M T H M; Van Deursen, C J; Pedrizzetti, G; Rodwell, L; Heymans, S R B; Nijveldt, R
Abstract: Introduction: The direction of blood flow in the left ventricle (LV) is determined by intraventricular pressure gradients (IVPGs) between apex and base, which are altered when cardiac function declines. New cardiac magnetic resonance (CMR) post-processing software enables estimating LV-IVPGs. To date, the prognostic value of CMR derived IVPGs in patients with dilated cardiomyopathy (DCM) remains unknown. Methods: DCM patients from the Maastricht Cardiomyopathy Registry, who underwent a CMR, were included. The software estimates the LV-IVPGs (between apex and base) by using the myocardial movement and velocity of a reconstructed 3D-LV model (derived from feature-tracking strain analysis of 2-, 3- and 4-chamber cine images). The primary outcome was a combined endpoint of heart failure (HF) hospitalisations, life-threatening arrhythmias and (sudden) cardiac death. Results: In total, 447 DCM patients were included (age 55 interquartile range [46–63] years; 60% male). During a median follow-up of 6 [4–9] years, 66 patients (15%) reached the primary endpoint. In 168 patients (38%), a temporary pressure reversal from base-apex to apex-base during the systolic-diastolic transition was observed (figure). After correction for covariates that were univariably associated with outcome (p<0.100, age, NYHA-class≥3, and left atrial (LA) conduit strain), flow reversal from base-apex to apex-base in the diastole was independently associated with outcome in the total cohort (HR 2.91, 95%-Confidence interval (95%-CI) [1.16–7.32], p=0.023; Table). In patients without pressure reversal (N=279) in the systolic-diastolic transition, IVPG during the total cardiac cycle (HR 0.88 [0.81–0.96], p=0.003), the systolic ejection force (HR 0.92 [0.87–0.97], p=0.003), and the E-wave decelerative force "C" (passive diastolic filling, HR 0.85 [0.74–0.97], p=0.013) were predictors of outcome, independent of other covariates (age, sex, NYHA class ≥3, LV ejection fraction, late gadolinium enhancement, LV longitudinal strain, LA volume index and LA conduit strain, table). Conclusion: CMR-derived LV-IVPG analysis showed pressure reversal in the systolic-diastolic transition in one-third of DCM patients, and flow reversal was an independent predictor of worse outcome in these patients. In patients without this pressure reversal, LV-IVPG during the total cardiac cyle, the systolic ejection force, and the E-wave decelerative force were predictors of outcome, independent of all evauluated clinical and imaging parameters. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Netherlands Cardiovascular Research Initiative (initiative with support of the Dutch Heart Foundation) and CVON (She-PREDICTS, grant 2017-21 & CVON-DCVA Double Dosis 2021)